Co-precipitation of Cathode Active Materials Precursors in Lithium-ion Batteries Recycling: Experiments and Modeling - Marco Vaccari; Federica Barontini; Antonio Bertei; Monica Puccini; Leonardo Tognotti (Chemical Engineering Transactions, 2023)
Recycling lithium-ion batteries (LIBs) is becoming an imperative task given the large flow of spent batteries that in the next future will have to be managed. Among the current three main recycling routes to convert spent LIBs into recycled products, that is, pyrometallurgy, hydrometallurgy, or direct recycling, the co-precipitation route lies between the last two routes: its key unit operations are the leaching of battery materials and the co-precipitation of a precursor for the re-synthesis of the cathode active material (CAM). High susceptibility to impurities in the leached solution and a strong link between high-quality CAM precursors and the composition of the dissolved metal salts, makes experimental analysis on spent LIBs a crucial step to find the best operating conditions. For this reason, we present an experimental campaign to study the co-precipitation and formation of the complex chemical compounds involved in the process. Moreover, we also exploit the support that rigorous models are giving in many industrial fields, also benefiting chemical engineering and laboratory analysis. Therefore, in this study we also present a rigorous simulation model on UniSim Design® with the thermodynamic package OLI® that enables the possibility to consider most of the different liquid-solid equilibria needed. A validation of the model is performed with experimental data and a sensitivity analysis on metal concentrations, pH, and chelating agent is performed to find the critical parameters that regulate the co-precipitation outcomes. The aim is to optimize the choice of operating conditions to limit the number of laboratory tests and complex analyses that are often expensive and time-consuming.